Outage Probability of a Cooperative Maximum Ratio Transmission - Erdogan, Eylem; Musta, Mahmut Sami; Gucluoglu, Tansal (IEEE, 2014)
In this paper, we present a cooperative communication system employing maximum ratio transmission technique and its outage probability performance over Rayleigh fading channels. Since maximum ratio transmission can achieve full diversity when used at tranmitters having multiple antennas while requiring no complexity increase at the receiver, the proposed system can be a preferable structure to be used both at the source and amplify-forward type relays of wireless networks to provide high speed and reliable transmission in practice. For this system, average end-to-end signal to noise ratio is analyzed mathematically, moreover, our computer simulation results show the error performance for several scenarios.
Keywords: maximum ratio transmission; cooperative communication; amplify-and-forward relaying; outage probability; PERFORMANCE; Engineering; Telecommunications